1998
DOI: 10.1021/jf970483z
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Determination of Galactose and Lactose in Honey

Abstract: Even when galactose and lactose are present in extraordinarily low concentrations in honey, both sugars are important constituents of this foodstuff because they might be useful in its characterization. Lactose and galactose determination in honey is also important because of the toxic effect of both sugars on honey bees. For the first time, a modification of the Boehringer-Mannheim GmbH enzymatic method is applied to 46 floral unpasteurized honeys for analyzing these sugars accurately, specifically, and quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The percentage of lactose was 4% in dandelion, 3% in multifloral and honeydew, and 2% in acacia and rhododendron honeys. Literature data show that lactose should be present in honeys only at very low concentration, approximately 0.01% [44]; in another previous work, lactose was monitored in honey samples by a different technique, but the authors did not provide data about the presence of this disaccharide in honey [42]. Among other carbohydrates, lactose and galactose are important compounds in honey because they might be useful for its characterization, although these sugars can be present at low concentration [44].…”
Section: Methods Applicationmentioning
confidence: 96%
See 1 more Smart Citation
“…The percentage of lactose was 4% in dandelion, 3% in multifloral and honeydew, and 2% in acacia and rhododendron honeys. Literature data show that lactose should be present in honeys only at very low concentration, approximately 0.01% [44]; in another previous work, lactose was monitored in honey samples by a different technique, but the authors did not provide data about the presence of this disaccharide in honey [42]. Among other carbohydrates, lactose and galactose are important compounds in honey because they might be useful for its characterization, although these sugars can be present at low concentration [44].…”
Section: Methods Applicationmentioning
confidence: 96%
“…Arabinose, xylose, ribose, mannose, galactose, and stachyose had concentrations below the MDL in all analyzed samples. Therefore, they were not used to characterize the honey samples in this study, although some previous studies reported that some of these compounds had detectable concentrations, e.g., one study carried out on honey samples from Spain showed that galactose had concentrations ranging between 0.0052 and 0.0151% [44]. Figure 3 reports the mean concentration and standard deviation of the saccharides, which can be related to the floral origin, in the 43 honey samples (23 multifloral, 4 acacia, 4 dandelion, 8 rhododendron, and 4 honeydew).…”
Section: Methods Applicationmentioning
confidence: 99%
“…In enzymatic methods for lactose detection, either glucose [by glucose oxidase (GOD) and peroxidase (HRP)] 2 or galactose (by galactose dehydrogenase) 3 have been detected optically after hydrolysis by b-galactosidase (GAL). An immobilisation procedure allows biological parts to be reused (enzymes, microbial cells, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The main sugars of honey are fructose and glucose, whose sum, together with sucrose content, are used as quality criteria for honeys within the European Union (OJEC, 2002). Honey also contains a complex A C C E P T E D M A N U S C R I P T mixture of other mono-, di-, tri-, oligo-and polysaccharides (Val et al, 1998;Bogdanov et al, 2008). Sugars contribute to the antibacterial properties of honey and its preservation, because they provide high osmolarity and low water activity, which makes microorganism growth difficult.…”
mentioning
confidence: 99%